A regional consensus recommendation on brain atrophy as an outcome measure in multiple sclerosis. Issue 1 (December 2016) - Alroughani, Raed; Deleu, Dirk; El Salem, Khalid; Al-Hashel, Jasem; Alexander, K.; Abdelrazek, Mohamed; Aljishi, Adel; Alkhaboori, Jaber; Al Azri, Faisal; Al Zadjali, Nahida; Hbahbih, Majed; Sokrab, Tag; et al.
Abstract Background Multiple sclerosis (MS) is a chronic autoimmune disease characterized by inflammatory and neurodegenerative processes leading to irreversible neurological impairment. Brain atrophy occurs early in the course of the disease at a rate greater than the general population. Brain volume loss (BVL) is associated with disability progression and cognitive impairment in patients with MS; hence its value as a potential target in monitoring and treating MS is discussed. Methods A group of MS neurologists and neuro-radiologists reviewed the current literature on brain atrophy and discussed the challenges in assessing and implementing brain atrophy measurements in clinical practice. The panel used a voting system to reach a consensus and the votes were counted for the proposed set of questions for cognitive and brain atrophy assessments. Results The panel of experts was able to identify recent studies, which demonstrated the correlation between BVL and future worsening of disability and cognition. The current evidence revealed that reduction of BVL could be achieved with different disease-modifying therapies (DMTs). BVL provided a better treatment and monitoring strategy when it is combined to the composite measures of "no evidence of disease activity" (NEDA). The panel recommended a set of cognitive assessment tools and MRI methods and software applications that may help in capturing and measuring the underlying MS pathology with high degree of specificity. Conclusion BVL was considered to be a useful measurement to longitudinally assess disease progression and cognitive function in patients with MS. Brain atrophy measurement was recommended to be incorporated into the concept of NEDA. Consequently, a consensus recommendation was reached in anticipation for implementation of the use of cognitive assessment and brain atrophy measurements on a regional level.